Penerapan Model Pembelajaran Discovery Learning untuk Meningkatkan Aktivitas Belajar Siswa Kelas XII MIPA 8 SMA Negeri 2 Makassar - Hajar, Abdul (Biology Teaching and Learning, 2021)
Abstract. Efforts to improve the quality of learning processes and outcomes through various optimal learning models need to be carried out by teachers in schools, where teachers play a very important role in preparing students to take part in learning. The purpose of this study was to determine: the application of the discovery learning model to improve student learning activities in class XII MIPA 8 SMA Negeri 2 Makassar. This research is a classroom action research, which investigates student factors, teacher factors and student learning activities. The location of this research is SMA Negeri 2 Makassar, class XII IPA 8 as many as 36 students in the Odd Semester of the 2019/2020 school year. Action implementation consists of 2 (two) cycles followed by activities: Planning, Action, Observation and Reflection. The results showed that by applying the discovery learning model of class XII MIPA 8 students could increase student learning activities. The increase in student activity is indicated by the increase in the percentage of student learning activeness. In the first cycle the percentage of student activity reached 40.27%, in the second cycle, the percentage of student activity increased to 76.38%. This shows that the percentage of student activity has increased and has reached the predetermined indicators of success. Keywords: discovery learning model, learning activity